Design and Validation of a Community Empowerment Perception Scale in Chilean University Students - Fierro Pérez, Lorena Andrea; Rodas Medina, Naomi Alejandra; Zambrano Constanzo, Alba Ximena (Revista de Psicología, 2020)
This study introduces the psychometric properties of an instrument built to evaluate the community empowerment perception of university students. The participants were 617 students of a state university in southern Chile. To determine the reliability of the Community Empowerment Perception Scale, Cronbach’s alpha was used, as well as exploratory factorial analysis (EFA) and confirmatory factorial analysis (CFA) for factorial validity. The results show the presence of five factor named: Participation, politization, self-management, power and control, and community identity, all of them with reliability greater than 0.80. For its part, the AFC confirmed that each of the five factors are explained by a single model, showing factorial loads that vary between 0.69 to 0.81. This scale represents a resource for the evaluation of the perception of community empowerment in a specific community, being a potential contribution in the field of higher education and community interventions, through its adaptation and validation in other contexts.